2020
DOI: 10.3126/banko.v30i2.33478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of invasive alien plant species on aquatic biodiversity of Koshi Tappu Wetlands : Ramsar Site, Nepal

Abstract: Koshi Tappu Wetlands play a significant role in the conservation of many rare and endangered species of flora and fauna. However, this wetland is threatened by several natural and anthropogenic stressors; among others, invasion by invasive species is the most serious problem. The objective of this study was to prepare an inventory list of wetlands, categorize the wetlands based on the coverage of alien species, identify the problematic aquatic invasive plant species, and assess their impact on water quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In Koshi Tappu Wildlife Reserve area 66 wetlands were recorded and 66.67% of which were impacted by invasive plants species. The most abundant invasive species were Echhornia and Ipomoea (Pandey et al 2020). Thapa et al (2020) found that in KTWR Shorea robusta was the dominant tree species with the IVI of 129.07.…”
Section: Discussionmentioning
confidence: 98%
“…In Koshi Tappu Wildlife Reserve area 66 wetlands were recorded and 66.67% of which were impacted by invasive plants species. The most abundant invasive species were Echhornia and Ipomoea (Pandey et al 2020). Thapa et al (2020) found that in KTWR Shorea robusta was the dominant tree species with the IVI of 129.07.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in Koshi Tappu Wild Life Reserve (KTWR) area, a Ramsar site, Ipomoea carnea subsp. fistulosa is the most problematic along with the Pontederia crassipes (Pandey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%